Industrial competitiveness and FDI opportunities in the metropolitan periphery - product space network analysis of Laval, Canada - Wang, Yihan; Turkina, Ekaterina; Lemay, Normand (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2023)
This paper investigates the industrial competitiveness and FDI opportunities in the metropolitan periphery embedded in the product space network. Assessing the knowledge complexity and revealed competitive advantage (RCA) of local industries, entrepreneurs and policymakers can identify the most prominent ones and implement competitive strategy accordingly. Complementarily, they can attract FDI inflows in non-RCA structural hole sectors of close knowledge proximity with existing RCA sectors in the product space network. In the case study of Laval, Canada, we conduct quantitative product space network analysis and qualitative thematic analysis on the semi-structured interviews with entrepreneurs and policymakers to address these points.